The Implementation of Sorogan Methods for Santri Islamic Boarding School in Classical Islamic Book (Kitab Kuning) (EDUKASIA, 2022)
THE IMPLEMENTATION OF SOROGAN METHODS FOR SANTRI   ISLAMIC BOARDING SCHOOL IN CLASSICAL ISLAMIC BOOK (KITAB KUNING). This study is to investigate the quality of students' literacy of Kitab Kuning through the Sorogan method. To collect the data, observation was conducted in twenty Pesantren in West Java and in-depth interviews with Kiai, santri, alumni, and some local societies around the pesantren. The data collected was then analyzed with a descriptive narrative. This study found that the level of santri’s literacy to understand Kitab Kuning decreased. It was aligned with the change of teaching methods from the Sorogan to the classical method. This issue has a negative impact on the process of transferring knowledge such as misconception to understand Islamic law.